Mendorong Inkulsi Keuangan Melalui Digital: Pendekatan Technology Acceptance Model (TAM) pada Nasabah Bank Syariah - Edy Prabowo; Fernando; Jesicca Valencia; Meiliana; Nabila Azzahra; Vallerina Mihairy; Welshan Fernando (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the role of digitalization in enhancing financial inclusion among customers of Bank Syariah Indonesia (BSI) using the Technology Acceptance Model (TAM) approach. The research focuses on how perceived ease of use and perceived usefulness of BSI Mobile’s digital banking services influence technology adoption, particularly at BSI Dumai Branch. This qualitative study employs a descriptive analysis method, with data collected through interviews, observations, and documentation. The findings indicate that the adoption of Islamic banking digitalization still faces several challenges, including low digital literacy, limited infrastructure, and the need for improved cybersecurity measures. However, the increase in BSI Mobile users from 2021 to 2022 suggests that digitalization has successfully expanded financial access and enhanced financial inclusion among customers. This study highlights the importance of socialization efforts, enhanced security features, and the optimization of digital services to improve user experience and accelerate the digital transformation of Islamic banking.